The effect of acute oral phosphatidic acid ingestion on myofibrillar protein synthesis and intracellular signaling in older males. Issue 3 (June 2019) - Smeuninx, Benoit; Nishimura, Yusuke; McKendry, James; Limb, Marie; Smith, Ken; Atherton, Philip J.; Breen, Leigh
Summary: Background: Age-related muscle loss (sarcopenia) may be driven by a diminished myofibrillar protein synthesis (MyoPS) response to anabolic stimuli (i.e. exercise and nutrition). Oral phosphatidic acid (PA) ingestion has been reported to stimulate resting muscle protein synthesis in rodents, and enhance resistance training-induced muscle remodelling in young humans. Purpose: This study examined the effects of acute oral PA ingestion on resting and exercise-induced MyoPS rates in older individuals. Methods: Sixteen older males performed a bout of unilateral leg resistance exercise followed by oral ingestion of 750 mg of soy-derived PA or a rice-flour placebo (PL) over 60 min post-exercise. A primed-continuous infusion ofl -[ring- 13 C6 ]-phenylalanine with serial muscle biopsies was used to determine MyoPS at rest and between 0–150 and 150–300 min post-exercise. Results: Plasma [PA] concentrations were elevated above basal values from 180 to 300 min post-exercise in PA only (P = 0.02). Exercise increased MyoPS rates above basal values between 150 and 300 min post-exercise in PL (P = 0.001), but not PA (P = 0.83). Phosphorylation of p70S6K, rpS6, 4E-BP1 and Akt was elevated above basal levels in the exercised leg over 150–300 min post-exercise for PL only (P = 0.018, 0.007, 0.011 and 0.002, respectively), and were significantly greater than PA (P < 0.01 for all proteins). The effects of oral PA ingestion on proteolytic signaling markers were equivocal. Conclusions: Acute oral phosphatidic acid ingestion appears to interfere with resistance exercise-induced intramuscular anabolic signaling and MyoPS in older males and, therefore, may not be a viable treatment to counteract sarcopenia.Clinicaltials.gov registration no:NCT03446924 .